PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS MENGGUNAKAN MODEL KOOPERATIF NUMBER HEADS TOGETHER DI SD - Rainy, November; Sukmawati, Sukmawati; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to determine the increase in activity and student learning outcomes by using cooperative model type number heads together in learning Social Sciences class VB SDN 34 Pontianak City. The research method used is descriptive. The form of research is Classroom Action Research. The subjects of this study, 1 teacher and students of VB SDN 34 Pontianak Kota class of 34 people. The average ability of teachers to plan lessons in the cycle I is 3.36 and cycle II to 3.95. The average ability of teachers to implement learning cycle I is 3.46 and cycle II to 3.92. Percentage of student learning activity in cycle I was 62,06% and cycle II to 81,76%. Average learning outcomes of students cycle I is 74.71 and in cycle II to 86.76. From the research results obtained conclusion that there is increasing activity and student learning outcomes by using cooperative model number heads together type in learning Social Sciences class VB SDN 34 Pontianak City.Keywords: Activity, Learning Outcomes, Cooperative